2023
DOI: 10.1371/journal.pone.0285314
|View full text |Cite
|
Sign up to set email alerts
|

The intake of ultra-processed foods, all-cause, cancer and cardiovascular mortality in the Korean Genome and Epidemiology Study-Health Examinees (KoGES-HEXA) cohort

Abstract: The relationship between ultra-processed food (UPF) intake and mortality is unknown in Asian countries, yet the intake of UPF is on the rise in these countries. This study examined the association of UPF intake with all-cause, cancer and cardiovascular disease (CVD) mortality. Participants were 113,576 adults who responded to a 106-item food frequency questionnaire during recruitment of the 2004–2013 Health Examinees (HEXA) study, a prospective cohort study in Korea. UPF were defined using the NOVA classificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 62 publications
2
10
0
Order By: Relevance
“…Interestingly, some have suggested the effect of UPFs may be more significant in women than in men, while others have reported no significant sex interaction for all-cause mortality [ 18 , 19 ] and incident CVD [ 14 ]. Similar to our study, Kityo et al [ 20 ] found no significant associations in both sexes for all-cause mortality. In this Korean population, the lower mortality rates may have been influenced by the middle-aged demographic and nutritional profile with a low UPF intake of 25.1%, and therefore the insignificant associations [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Interestingly, some have suggested the effect of UPFs may be more significant in women than in men, while others have reported no significant sex interaction for all-cause mortality [ 18 , 19 ] and incident CVD [ 14 ]. Similar to our study, Kityo et al [ 20 ] found no significant associations in both sexes for all-cause mortality. In this Korean population, the lower mortality rates may have been influenced by the middle-aged demographic and nutritional profile with a low UPF intake of 25.1%, and therefore the insignificant associations [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our study, Kityo et al [ 20 ] found no significant associations in both sexes for all-cause mortality. In this Korean population, the lower mortality rates may have been influenced by the middle-aged demographic and nutritional profile with a low UPF intake of 25.1%, and therefore the insignificant associations [ 20 ]. Studies have also demonstrated that a higher UPF intake was more associated with hypertension, type 2 DM, and obesity for women compared to men [ 8 10 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“… 19 , 20 One recent prospective cohort study showed that total UPF consumption was not associated with the risk of CVD mortality. 21 To further investigate the dose–response relationship between UPF consumption and the risk of CVEs, we conducted a systematic review and meta-analyses of articles that reported the CVEs in corresponding clinical studies. 22 …”
Section: Introductionmentioning
confidence: 99%